Are females in good condition better able to cope with costly males?. (25th April 2018) - Iglesias-Carrasco, Maider; Jennions, Michael D; Zajitschek, Susanne R K; Head, Megan L
Abstract : The net gains females obtain from mating might depend on both her phenotype and that of her mate. We manipulated male and female conditions to determine their effects on mating behavior and fitness. Females mated with males in better condition started dislodging males sooner and had shorter copulations than females mated to poor condition males. However, there was no detectable fitness cost to females of mating with males in poorer condition. Females may ameliorate the costs of mating by altering their behavior. Abstract: The costs of mating for a female might depend on both her phenotype and that of her mate. Sexually antagonistic male traits that negatively affect females are often condition dependent, so a male's rearing environment can affect the costs he imposes on his mate. Likewise, a female's ability to resist male-imposed costs might be condition dependent. We experimentally manipulated female and male body conditions in the seed beetle Callosobruchus maculatus by rearing larvae on a good or poor quality diet. We then tested whether the cost of mating for a female (measured as copulation behaviors associated with sexual conflict as well as her fecundity and survival) depended on her and/or her mate's body condition. As expected, females in better condition laid more eggs and lived longer, indicating higher fitness. More interestingly, females that mated with males in better condition had shorter copulations and started to kick sooner. Both results are potentially indicative of greater sexual conflict. We suggest that these changes in mating behavior might be driven by the higher toxicity of ejaculates of males that are in better condition. Crucially, however, the lack of any interaction between male and female conditions for the variables measured suggests that any increase in the costs of mating with a male in better condition is not ameliorated by the female's own condition.